Influence of Anthropogenically-Forced Global Warming and Natural Climate Variability in the Rainfall Changes Observed Over the South American Altiplano - Vera, Carolina S.; Díaz, Leandro B.; Saurral, Ramiro I. (Frontiers in Environmental Science, 2019)
Changes in the summer rainfall and 200-hPa zonal winds (U200) in the South American Altiplano are studied from 1902 to 2018 using three different reanalysis datasets and simulations from 14 climate models of the fifth phase of the Coupled Model Intercomparison Project (CMIP5). No significant trend in rainfall was identified from GPCC reanalysis data over that period. On the other hand, regional U200 trends estimated from 20C and ERA20C reanalyses and from CMIP5 Historical simulations are significant and positive over the 1902-2005 period. However, the trends seem to be dependent on the reanalysis dataset and period considered. While no significant U200 trend is detected in simulations forced only by external natural sources, the mean trend is positive and significant in simulations forced only by the increment of anthropogenic greenhouse gas emissions. Therefore, a signal associated with the anthropogenic forcing of climate change has been detected in U200 trends in the Altiplano, but it is weak as compared with the internal climate variability. Singular value decomposition analyses based on both reanalyzed and simulated data were performed to describe the co-variability between rainfall in the Altiplano, regional U200 and global sea surface temperature (SST). The analysis confirms that negative rainfall anomalies in the Altiplano, associated with positive U200 anomalies, are related with positive SST anomalies mainly in the tropical Pacific-Indian Oceans. Simulations can reproduce observed relationships and confirm that natural variability explains the observed year-to-year variability. Simulations also confirm that anthropogenic forcing is a necessary condition to explain the positive trends detected in the co-variability between tropical SST and regional U200 anomalies. However, the large influence exerted by the South American Monsoon over the region can also affect sign and magnitude of the changes in the Altiplano. No significant relationship was found from CMIP5 simulations between poleward displacements of the global Hadley cell and regional U200 changes. Instead, South American Hadley cell displacements are significantly correlated with regional U200 changes. The latter might be an additional evidence of the combined influence of both tropical surface ocean and South America Monsoon on the circulation changes in the Altiplano in the global warming context.